Business Plan for Affordable Student Housing in Georgia - Vardania, Davit; Dvouletý, Ondřej; Válek, Lukáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Abstract: The purpose of this bachelor’s thesis is to create an overall business plan for low-cost student housing in Georgia that addresses the growing need for affordable, energy-efficient housing. The first stage in the study examines socio-economic and demographic factors affecting the housing market by relating to the needs of students. Market assessment, financial modeling, and risk analysis were used to identify viable business opportunities using a mixed-method approach. The evaluation of market dynamics, construction of a sustainable operational model, and integration of eco-friendly design practices in housing development were key processes. Results show how an affordable student housing project can be feasible given strategic funding, energy-efficient construction, and innovative operating tactics. A strong financial viability of the proposed business model is shown by positive revenue projections and return on investment (ROI). Finally, the conclusions highlight the importance of sustainability and policy consideration in addressing housing challenges and suggest ways to scale the model to other regions.
Vedoucí práce: Ondřej Dvouletý
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses